2014
DOI: 10.1093/jis/14.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influence of the antibiotic ciprofloxacin in the development of an Old World screwworm fly, Chrysomya putoria

Abstract: Chrysomya putoria (Wiedemann) (Diptera: Calliphoridae), an Old World screwworm fly, is a species with potential for maggot therapy practice and has been described in myiasis and forensic entomology studies. The objective of the present study was to assess the action of different ciprofloxacin concentrations on the growth and development of C. putoria . First instar maggots of the third generation were raised on 60 g of chicken gizzard homogenate in 65% agar diet and received ciprofloxacin chloridrate. Each con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…On this subject, Ferraz et al . (, b; ) tested the development of C . putoria using a diet‐containing antibiotics (ampicillin, gentamicin and ciprofloxacin) in different concentrations, to study the species' growth rate under the effect of these substances.…”
Section: Introductionmentioning
confidence: 99%
“…On this subject, Ferraz et al . (, b; ) tested the development of C . putoria using a diet‐containing antibiotics (ampicillin, gentamicin and ciprofloxacin) in different concentrations, to study the species' growth rate under the effect of these substances.…”
Section: Introductionmentioning
confidence: 99%
“…Fascinating studies on insect growth and development have uncovered that ciprofloxacin possesses the ability to neutralize Bacillus sphaericus, thereby fostering the proliferation of Aedes (Stegomyia) aegypti larvae [24]. Similarly, in the realm of Chrysomya pretoria, Ferraz et al [25] unearthed a stimulatory effect of ciprofloxacin on growth. Conversely, the metamorphosis of Anopheles barbirostris (Diptera: Culicidae) from larvae to adult is notably hindered by the administration of ciprofloxacin [26].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, most of the studies have focused on the fitness consequences of adding of these drugs to the food of laboratory cultured insects (Büyükgüzel & Kalender, 2008;Ridley et al, 2013;Xu et al, 2016). At low concentrations of ciprofloxacin (3.33 to 13.33 µg/mL), the development of the fly Chrysomia putoria was not altered (Ferraz et al, 2014), while addition of streptomycin to the food at concentrations of 0.03 to 0.15% increased the growth of the larvae of the butterfly Spodoptera litura, without affecting its survival (Thakur et al, 2016). Dickel et al (2016) reported that long-term exposure to prophylactic treatments (fumagillin) negatively affects the number of eggs laid by females of the wood tiger moth Parasemia plantaginis.…”
Section: Introductionmentioning
confidence: 99%